2018
DOI: 10.1093/jac/dky379
|View full text |Cite
|
Sign up to set email alerts
|

High efavirenz serum concentrations in TB/HIV-coinfected Ugandan adults with a CYP2B6 516 TT genotype on anti-TB treatment

Abstract: A large proportion of our study participants had at least one efavirenz serum concentration >4 mg/L. The CYP2B6 516 TT genotype was the strongest predictor of high concentration. Physicians should be vigilant that efavirenz serum concentrations may be elevated in patients on concomitant anti-TB treatment and that individualized care is warranted whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with a study by Chirehwa et al, who reported a 54% increase in isoniazid acetylation clearance in patients on efavirenz (25), and another by Bhatt et al, who demonstrated a 29% decrease in isoniazid concentrations in patients on efavirenz (8). Efavirenz concentrations in this cohort of SOUTH study patients have previously been reported to be higher than in other populations (26), so the effect of efavirenz coadministration may even be amplified compared to previous reports. The mechanism for this decrease in concentrations is still unclear and needs to be evaluated; it could be due to the induction of drug-metabolizing enzymes or the effect on an efflux pump or uptake transporter.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with a study by Chirehwa et al, who reported a 54% increase in isoniazid acetylation clearance in patients on efavirenz (25), and another by Bhatt et al, who demonstrated a 29% decrease in isoniazid concentrations in patients on efavirenz (8). Efavirenz concentrations in this cohort of SOUTH study patients have previously been reported to be higher than in other populations (26), so the effect of efavirenz coadministration may even be amplified compared to previous reports. The mechanism for this decrease in concentrations is still unclear and needs to be evaluated; it could be due to the induction of drug-metabolizing enzymes or the effect on an efflux pump or uptake transporter.…”
Section: Discussionsupporting
confidence: 93%
“…Increasing interest in CYP2B6 genetic polymorphism has been stimulated by revelations of a specific CYP2B6 genotype that significantly affects the metabolism of various drugs in common clinical use in terms of increasing drug efficacy and avoiding adverse drug reactions (Yuce-Artun et al, 2014). In recent years, the research on CYP2B6 gene polymorphism has focused on its pharmacokinetic and pharmacodynamic effects on the chemotherapy drug cyclophosphamide (Shu et al, 2017), the anesthetics ketamine (Wang, Neiner, & Kharasch, 2018), the central nervous system-active bupropion (Tomaz et al, 2015) and methadone (Ahmad, Valentovic, & Rankin, 2018), and the antiretroviral drug efavirenz (von Braun et al, 2018). In addition, the distribution of CYP2B6 genotypes have been studied in several different populations (Szalai, Hadzsiev, & Melegh, 2016;Yuce-Artun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of RIF, INH, ethambutol, and pyrazinamide were measured at 1, 2, and 4 hours postdosing. EFV (600 mg) was measured at 12 ± 2 hours postdosing, but the results of genetic variants and EFV exposure have been reported separately . Patients with undetectable 2‐hour concentrations were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…EFV (600 mg) was measured at 12 ± 2 hours postdosing, but the results of genetic variants and EFV exposure have been reported separately. 39 Patients with undetectable 2-hour concentrations were excluded from the analysis. The pharmacokinetic analyses were performed with high-performance liquid chromatography, and AUCs were estimated using noncompartmental analysis.…”
Section: Methodsmentioning
confidence: 99%